PENGARUH BEBERAPA DOSIS LIMBAH CAIR PABRIK KELAPA SAWIT DAN MEDIA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) FASE MAIN NURSERY - Amri, Al Ichsan; Indiarto, Asko '; ', Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Research on effects of some dose of palm oil mill effluentand media on the growth of oil palm Seedlings( Elaeisguineensis Jacq .) fase main nursery, plantation experiment have been conducted in garden experiment of the Agriculture Faculty, Riau University was startedon march  until june 2015. with the aim to get the dose of palm oil mill effluent and media works best for seedlings growth palm oil. A field experiment was conducted by using split plot design, in which three levels of media ie; Ultisol ,Histosol , and mixure, were assigned to main plot and four levels of palm oil mill effluentie; control , 0.8 l , 1.6 l , and 2.4 l. The Parameters observed were plant height, leavesnumber, the increase in diameter stump,root volume, root crown ratio, dry seedling weight.Based on research results that palm oil mill effluent 2.4 l in a media mixure show results in best than other treatment to increase plant height,diameter stump, root crown ratioon palm oil in  main nursery.   Keywords :palm oil mill effluent, media, oil palm Seedlings